Identifying Training, Diagnostic and Therapeutic Needs From a Comparison in the Distribution of Vestibular Disorders in Primary Care and in a Neurotology Unit - Domínguez-Durán, Emilio; Moreno-de-Jesús, Carolina; Prieto-Sánchez-de-Puerta, Lucía; Mármol-Szombathy, Irene; Sánchez-Gómez, Serafín (Frontiers in Neurology, 2020)
Introduction: Several epidemiological studies in Neurotology have been previously carried out in the general population. This approach is useful for learning about the most common disorders in clinical population, but it may fail when one is trying to help professionals to guide their training, to optimize their resources and to decide on the highest-priority research objectives. Objective: To identify which of the neurotological diseases are most common in two different populations, those who attended a consultation in the Neurotology Unit of a tertiary level hospital and those who did so in Primary Care in order to infer which of them requires more attention in each context and their specific needs. Methods: All the diagnoses made in Hospital Care between October 15, 2017 and October 14, 2018 were reviewed. These diagnoses were coded and classified into syndromes and diseases. Later, the proportions of each category were compared with the proportions of the neurotological diagnoses made in five Primary Care centers over the same period of time. Results: BPPV is the most common cause of vestibular symptoms in both contexts. Vestibular migraine, ischemic vestibular symptoms, orthostatic hypotension and side effects of drugs are common in Primary Care, whereas Ménière’s disease and undifferentiated episodic vestibular syndrome are common in specialized centers. Conclusion: The proportion of diagnoses in neurotologic patients is different in the general population and in the specialized center population, and therefore they have different needs. Primary Care professionals would benefit from training on maneuvers for repositioning otoliths, the treatment of headache, the identification of cardiovascular risk factors, the orthostatic hypotension and the side effects of the most commonly used drugs. The professionals who work in specialized centers need strategies for dealing with cases of BPPV associated to other vestibular diseases and refractory cases and their research should focus on the development of new diagnostic tools for the diagnosis of undifferentiated episodic vestibular syndrome and new therapeutic options for Ménière’s disease.